2012
DOI: 10.1186/1471-2458-12-369
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and treatment delay among Tuberculosis patients in Afar Region, Ethiopia: A cross-sectional study

Abstract: BackgroundTB is a major public health problem globally and Ethiopia is 8th among the 22 high burden countries. Early detection and effective treatment are pre-requisites for a successful TB control programme. In this regard, early health seeking action from patients’ side and prompt diagnosis as well as initiation of treatment from the health system’s side are essential steps. The aim of this study was to assess delay in the diagnosis and treatment of TB in a predominantly pastoralist area in Ethiopia.MethodsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
104
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(143 citation statements)
references
References 12 publications
24
104
15
Order By: Relevance
“…Two studies conducted in two different settings at different time period documented similar findings of patient delay (60 days) [8] [15]. Whereas another two studies conducted in a population of similar setting reported significantly different patient delays (20 versus 60 days) [3] [8]. Other studies from Tigray region and Wollega zone showed 53% and 62% of TB patients delay for diagnosis respectively [4] [5].…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Two studies conducted in two different settings at different time period documented similar findings of patient delay (60 days) [8] [15]. Whereas another two studies conducted in a population of similar setting reported significantly different patient delays (20 versus 60 days) [3] [8]. Other studies from Tigray region and Wollega zone showed 53% and 62% of TB patients delay for diagnosis respectively [4] [5].…”
Section: Introductionmentioning
confidence: 71%
“…First visit to government clinics/health post, health centers and private health facilities, patient with good functional status, patients in contact with more than two health providers associated with health service's delay [3] [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations